Reasons for Stop/Reduce Alcohol Consumption Scale: Psychometric Properties - Conde, Karina; Lichtenberger, Aldana; Peltzer, Raquel Inés; Cremonte, Mariana (Revista de Psicología, 2016)
The aim of this study was to evaluate the psychometric properties of a scale of motives to cease or reduce alcohol consumption in university students in terms of dimensionality, item level, internal consistency, and concurrent validity. The sample was constituted by 377 psychology students from the Universidad Nacional del Mar del Plata. Through an anonymous and confidential questionnaire, motives to cease or reduce alcohol consumption were enquired with a 20-item scale developed from qualitative answers, and as validation criteria, the habitual alcohol quantity consumed and the motivation to change ruler. Exploratory and confirmatory factorial analyses, reliability and bivariated analysis were performed. The exploratory and confirmatory factorial analyses pointed to a three-dimensional structure labeled as alcohol rejection, health and vital changes, and severe consequences of alcohol consumption. Reliability coefficients were satisfactory. Relationships were found between the first two dimensions and the quantity of alcohol consumed, and between motivation to change and health and vital changes dimension. The difference between hypothetical and real motives for change and the role of severe consequences of alcohol consumption in groups of higher alcohol consumption are discussed.